Perception and Participation of The Community on The Sustainable Fisheries Agribusiness Development Program in Sungai Gerong, South Sumatera - Raty Austin; Indah Widiastuti; Marini Wijayanti (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze the perception and participation of the community, as well as to analyze the factors of community perception that influence their participation in the Belida Musi Lestari CSR Program; a project for the conservation of belida fish and the development of sustainable fisheries agribusiness. This study uses descriptive quantitative method and inferential statistical through an observational survey, interviews and questionnaires to 100 respondents from the productive age community in Sungai Gerong Village, Banyuasin Regency, South Sumatera Province and was conducted in September-October 2025. Perception and participation levels were analyzed using a Likert scale, with the results grouped into five categories. Multiple linear regression analysis was then conducted to determine the perceptual factors influencing participation. The results showed that the community had a positive perception of the program and actively participated in the program. The results of multiple linear regression analysis show that all perception variables simultaneously have a signifficant effect on community participation at all stages of the program. Partially, the perception variable of expected economic benefits only has a signifficant effect at the program planning stage; while perceptions of the relational quality between the company and the community and the technical aspects of sustainability have a signifficant effect on community participation starting from the planning stages, implementation stage to the program monitoring stage.